Effect of farm to fork operations on bioactive compounds in white-fleshed and color-fleshed potatoes - Amer, Fauzi Saleh Massoud, author; Vanamala, Jairam, advisor; Stone, Martha, advisor; Reddivari, Lavanya, committee member; Holm, David, committee member (Colorado State University. Libraries, 2015)
The potato, Solanum tuberosum L., is one of the most commonly consumed food crops worldwide, and is the leading vegetable crop in the United States with 69% of per capita consumption as processed potatoes. In addition to micro- and macro-nutrients, color-fleshed potatoes are one of the richest plant sources for health promoting components such as resistant starch, polyphenols, and carotenoids. In contrast, potatoes are well known to contain naturally occurring glycoalkaloids (GA; α-chaconine and α-solanine) and processing-induced acrylamide (AL). Potatoes can be stored up to one year before being processed/consumed and the effect of genotype, storage (4°C or 10°C; 3 or 6 months) and processing (baking and frying) on both toxic and health beneficial compounds remains unknown. We hypothesized that cultivar, storage and processing alters bioactive content in potato tuber and potato products. To test this hypothesis, raw, baked, and chipped of white-, yellow-, red-, and purple-fleshed potatoes from initial (fresh) and stored tubers were evaluated for AL/vitamin C and GAs using Ultra Performance Liquid Chromatography (UPLC) and High Performance Liquid Chromatography-Diode Array Detector (HPLC-DAD/UPLC-DAD), respectively. Total phenolic content (Folin - Ciocalteu reducing), anthocyanin content (pH differential method), antioxidant activity (DPPH and ABTS assay) were also determined. Raw potatoes were analyzed for reducing sugars (glucose and fructose) using a spectrophotometer. Sensory attributes (9-point hedonic scale) of baked and potato chips were assessed using untrained consumer panelists (n= 94 – 114). The content of GA/AL increased with storage, dependent on cultivar. Reducing sugar content in raw potatoes increased with storage, thereby, AL content in potato chips positively correlated with reducing sugars. Purple-fleshed potatoes had higher (p ≤ 0.05) total phenolic content, anthocyanin content, and antioxidant activity than red-fleshed potatoes and white-fleshed potatoes. The interaction effect of storage time and temperature on total phenolic content, anthocyanin content, and antioxidant activity was genotype-dependent. Baking led to a significant (p ≤ 0.05) increase in total phenolic content, anthocyanin content, and antioxidant activity; whereas chipping led to significant losses in total phenolic content, anthocyanin content, and antioxidant activity. However, red- and purple-fleshed potatoes could serve as potential sources of non-nutrient health-benefiting compounds in the human diet even after storage and processing. Vitamin C content in potato tubers and processed potatoes was genotype-dependent. Vitamin C content rapidly declined with storage after six months of storage irrespective of storage temperature (4°C or 10°C). Chipping and frying resulted in significantly reduced vitamin C levels compared to baked potatoes and unprocessed potatoes among all tested cultivars. An increase in GA and AL content, bioactive compounds, and antioxidant activity found with storage was cultivar dependent. However, vitamin C decreased with storage. Thus, it is critical to measure GA and AL content not only in the fresh tubers but also in the final potato products such as baked and chipped potatoes. It is critical to adjust food systems processes to consistently deliver lower GA and AL content, while retaining the beneficial bioactives, vitamin C, and sensory attributes of the final potato products. Adjusting farm-to-fork operations to retain the health-benefiting compounds in food crops while reducing natural and process-induced toxicants will aid in countering growing epidemic of chronic diseases globally.